STRATEGI PRESERVASI ARSIP STATIS DALAM RANGKA MENJAMIN KELESTARIAN ARSIP STATIS SEBAGAI MEMORI KOLEKTIF BANGSA PADA LEMBAGA KEARSIPAN: Array - Azmi Azmi (Arsip Nasional Republik Indonesia, 2010)
It is stated on the Act Number 43 of 2009 concerning Archives that due to their locale of jurisdiction, archival institutions retain functions, duties, and responsibilities in the field of archives management. The objective is to assure the safekeeping of archives as national responsibility for society, state and nation. Therefore, archival institutions must have commitment to acquire safety and sustainability of archives which is being managed. Generally, Archival institutions experience some inadequacies in performing archives management as their functions and duties. Namely, Formal policies on archives preservation have not been formed, stakeholders development has not been optimized, socializations are limited, resources (human, infrastructures, budgets) are restraint, and also archival partnerships have not been maximized yet. In contrast, the number of archives are increasing since the reformation of Indonesian government system. Archives are consigned by creators to not only local and national archival institutions, but also to high education institutions. These resulted complexicity on archives preservation and difficulties in fulfilling the prerequisite of archival public access as collective memory of the nation. Also, globalized information, knowledge development, archival practise encourage it. In reference to the circumstances, commitment on archives preservation should be established by authorities of every archival institutions level. It can be built by organizing strategies on archives preservation at their institutions. The strategies hold national archives framework system, including visions, missions, and work target. They grasp seven important aspects of archives management, namely guidelines/standards, stakeholders and human resources development, modernization, infrastructures, socializations, partnership, and fund.